The Condition of Non-Removable Dentures and the Surrounding Gum in The Supporting Teeth and Implants in the Presence of Milled Metal and MetalFree Frames in the Prostheses (Progress Annals: Journal of Progressive Research, 2023)
In modern dentistry, there is a tendency to replace the technology of wax modeling and metal casting with the technology of milling metal frames of prostheses from factory blocks [1, 3, 6, 7]. In addition, metal-free prosthesis designs are being actively introduced, manufactured mainly using two technologies: pressing and CAD/CAM milling [2, 4, 5]. Comparative studies of the clinical effectiveness of these fixed prosthesis designs are relevant. The purpose of the study is to conduct a comparative analysis of the results of non– removable prosthetics using modern structural materials: metal ceramics on milled and cast chrome-cobalt frames, pressed ceramics, ceramics on zirconium oxide frames.